Utilização de biomarcadores no diagnóstico precoce de lesão renal aguda em pacientes criticamente enfermos: revisão sistemática da literatura - Luana Amaral Pedroso (2017)
Acute kidney injury (AKI) is a common complication in hospitalized patients, with higher frequency in intensive care units (ICU). AKI is associated with a significant increase in morbimortality and health care expenditure. It is usually detected by measuring urine output and serum creatinine, which, due to several factors, are late markers. New circulating and urinary biomarkers emerged in recent decades as promising in the early diagnosis of AKI. Given its potential benefits in the diagnosis and prognosis of AKI, the need of using these new biomarkers in clinical practice is consensual. This study aims to perform a systematic review of literature, including studies published in MEDLINE (by PubMed), Lilacs (by BVS), CINAHL, COCHRANE and EMBASE that evaluated the performance of biomarkers for the early diagnosis of AKI, defined by the AKIN or KDIGO criteria, in patients admitted to the ICU. The review will include experimental and observational studies, published between 2006 and 2016, involving patients with 18 years or older more admitted to an ICU. Data extraction and analysis will be performed by two independent reviewers and disagreements analyzed by a third reviewer. Eight studies were selected. The main biomarkers investigated were neutrophil gelatinase-associated lipocalin (NGAL 5 studies), L-type fatty acid binding protein (L-FABP 2 studies), n-acetyl--dglucosamine (NAG 2 studies) and cystatin C (2 studies). In 73.9% tests performed by the studies have used urine samples. The biomarkers that presented the highest sensitivity (s) and specificity (sp) profile were the heat shock protein-72 (s=100%, sp=90%) and interleukin 18 (s=92%, sp=100%). Cystatin C showed poor performance in two studies. Overall, two studies presented unfavorable results for the use of biomarker because their levels were significantly affected by comorbidities even in the absence of AKI. All biomarkers have suffered some influence of other factors, such as comorbidities or etiology of AKI. An understanding of a single biomarker is unable to help identifying the etiology and mechanisms of AKI, but it helps in identifying and implementing effective strategies